A course of hydrotherapy exercises on varicose veins pain in postmenopausal women with multiple sclerosis - Saeid Charsouei; Nafiseh Sheghaghi; Dara Alvandfar (Mashhad University of Medical Sciences, 2021)
Introduction: Since varicose veins pain in MS patients are much more than others and these two factors have a detrimental effect on the quality of life of these women during menopause and on the other hand due to the positive effects of non-pharmacological methods such as hydrotherapy, this study was performed with aim to investigate a course of hydrotherapy exercises on varicose veins pain in postmenopausal women with multiple sclerosis. Methods: This randomized controlled clinical trial study was performed in 2019 on 24 postmenopausal women with multiple sclerosis with varicose veins pain in Sina Hospital of Tabriz. The subjects were randomly divided into control and intervention groups. The intervention group performed 24 sessions (eight weeks) the exercises in the pool for one hour each time. Pain intensity was measured before the study and one month after the end of the study. Data were analyzed by SPSS software (version 21) and dependent and independent t-tests. P<0.05 was considered statistically significant. Results: After the end of the intervention, it was found that pain intensity in the intervention group significantly reduced (P=0.001), while pain intensity in the control group did not change significantly (P=0.298). Comparison of pain intensity at the end of the study between the two groups showed that the pain intensity was significantly lower in the intervention group compared to the control group (P=0.001). Conclusion: Exercise in water has led to positive effects in reducing the severity of varicose veins pain in postmenopausal women with multiple sclerosis.